Streptococcus Mutans Membrane Vesicles Enhance Candida albicans Pathogenicity and Carbohydrate Metabolism - Ruixue Wu; Ruixue Wu; Guxin Cui; Guxin Cui; Yina Cao; Yina Cao; Wei Zhao; Wei Zhao; Huancai Lin; Huancai Lin (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus mutans and Candida albicans, as the most common bacterium and fungus in the oral cavity respectively, are considered microbiological risk markers of early childhood caries. S. mutans membrane vesicles (MVs) contain virulence proteins, which play roles in biofilm formation and disease progression. Our previous research found that S. mutans MVs harboring glucosyltransferases augment C. albicans biofilm formation by increasing exopolysaccharide production, but the specific impact of S. mutans MVs on C. albicans virulence and pathogenicity is still unknown. In the present study, we developed C. albicans biofilms on the surface of cover glass, hydroxyapatite discs and bovine dentin specimens. The results showed that C. albicans can better adhere to the tooth surface with the effect of S. mutans MVs. Meanwhile, we employed C. albicans biofilm-bovine dentin model to evaluate the influence of S. mutans MVs on C. albicans biofilm cariogenicity. In the S. mutans MV-treated group, the bovine dentin surface hardness loss was significantly increased and the surface morphology showed more dentin tubule exposure and broken dentin tubules. Subsequently, integrative proteomic and metabolomic approaches were used to identify the differentially expressed proteins and metabolites of C. albicans when cocultured with S. mutans MVs. The combination of proteomics and metabolomics analysis indicated that significantly regulated proteins and metabolites were involved in amino acid and carbohydrate metabolism. In summary, the results of the present study proved that S. mutans MVs increase bovine dentin demineralization provoked by C. albicans biofilms and enhance the protein and metabolite expression of C. albicans related to carbohydrate metabolism.